Green Eco-Friendly Paver Blocks Integrating Textile Dyeing Effluent Sludge (TDES) alongside Raw River Water Influent Sludge (RRWS) - Goh, Wan Inn; Low, Ci Yi; Wong, Khiing Yung; Suraiadi, Ikmal Danial; Qadir Bux alias Imran Latif (International Journal of Sustainable Construction Engineering and Technology, 2026)
The growing emphasis on sustainable construction materials has led to the exploration of industrial waste as viable alternatives. This study investigates the use of textile dyeing effluent sludge (TDES) and raw river water influent sludge (RRWS) in the production of eco-friendly paver blocks, aiming to promote sustainability while maintaining structural performance. Paver blocks were prepared with varying proportions (5%, 10%, 15%, and 20%) of TDES and RRWS to assess their impact on physical, chemical, and mechanical properties. Physical characterization included specific gravity and particle size analysis, while chemical composition was examined using X-ray Diffraction (XRD) and Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX). Mechanical testing evaluated compressive strength, density, water absorption, and initial rate of absorption. A control mix was used for comparison. TDES exhibited a low specific gravity (0.87), indicating poor suitability for structural applications. In contrast, RRWS showed greater stability (1.91), with particle grading favorable for flexibility. XRD and SEM-EDX confirmed the presence of cementitious compounds like silicon oxide (SiO₂) and calcite (CaCO₃), supporting the potential for partial replacement of traditional materials. Results showed that increasing TDES and RRWS content led to reduced compressive strength and increased porosity. However, the 5% RRWS mix achieved a compressive strength of 47.58 MPa, only slightly lower than the control (52.65 MPa), suggesting viable use at lower concentrations. In conclusion, the incorporation of TDES and RRWS in paver blocks presents a promising approach to recycling industrial sludge and enhancing the sustainability of construction materials. Optimal performance was observed at 5% RRWS content, balancing environmental benefits and mechanical integrity.